2017
DOI: 10.4103/0366-6999.213959
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Macular and Retinal Nerve Fiber Layer Thickness in Children with Refractory Amblyopia after Femtosecond Laser-assisted Laser In situ Keratomileusis

Abstract: Background:Localized macular edema and retinal nerve fiber layer (RNFL) thinning have been reported shortly after laser in situ keratomileusis (LASIK) in adults. However, it is still unclear how LASIK affects the retina of children. This study aimed to investigate the macular retina and RNFL thickness in children with refractive amblyopia who underwent femtosecond laser-assisted LASIK (FS-LASIK).Methods:In this study, we included 56 eyes of 32 patients with refractive amblyopia who underwent FS-LASIK in our ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
3
7
0
1
Order By: Relevance
“…It is also consistent with a previous study in which suction had no significant clinical effects on the macular thickness and RNFL thickness during FLEx or FS-LASIK [10]. However, it was demonstrated in another study that the average foveal and parafoveal retinal thicknesses were significantly thicker 1 day after surgery [11]. And the changes were reversible and recovered within 1 week without effect on the visual acuity [11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is also consistent with a previous study in which suction had no significant clinical effects on the macular thickness and RNFL thickness during FLEx or FS-LASIK [10]. However, it was demonstrated in another study that the average foveal and parafoveal retinal thicknesses were significantly thicker 1 day after surgery [11]. And the changes were reversible and recovered within 1 week without effect on the visual acuity [11].…”
Section: Discussionsupporting
confidence: 91%
“…However, it was demonstrated in another study that the average foveal and parafoveal retinal thicknesses were significantly thicker 1 day after surgery [11]. And the changes were reversible and recovered within 1 week without effect on the visual acuity [11]. We speculated the disparity of age accounts for the difference as the age is 9.68 ± 2.56 years in previous study compared to 21.00 ± 2.47 years in ours.…”
Section: Discussionmentioning
confidence: 48%
“…Suction during surgery and high IOP caused disorder of optic nerve axoplasm and malnutrition of retinal ganglia cells [9]. Nevertheless, research in children revealed that MT was thicker 1 day after surgery, but RNFL unchanged [22]. Another research found RNFL was thicker 3 months after LASIK, especially in the inferior-temporal sector [23], which was similar to our results, but the possible mechanism in it was still not clear.…”
Section: Discussionsupporting
confidence: 77%
“…Suction during surgery and high IOP caused disorders of the optic nerve axoplasm and malnutrition of retinal ganglia cells [11]. Nevertheless, research in children revealed that MT was thicker 1 day after surgery, but RNFL remained unchanged [22]. Another study found that the RNFL was thicker 3 months after LASIK, especially in the inferior-temporal sector [23], which was similar to our results, but the possible mechanism is still not clear.…”
Section: Discussionsupporting
confidence: 80%